2017
DOI: 10.1097/qai.0000000000001232
|View full text |Cite
|
Sign up to set email alerts
|

Brief Report: Soluble CD163 in CMV-Infected and CMV-Uninfected Subjects on Virologically Suppressive Antiretroviral Therapy in the ICONA Cohort

Abstract: CMV coinfection could be a major driver of monocyte/macrophage activation in virally suppressed HIV+ individuals and might explain the increased risk of non-AIDS morbidity/mortality in HIV/CMV-coinfected subjects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 48 publications
0
5
1
Order By: Relevance
“…Differences in the composition of the gut microbiome, for example, caused by specific sexual practices or frequent antibiotic use could hypothetically contribute to the lower CD4/CD8 ratios we observed in MSM. Contrary to our findings, previous studies, but conducted only in HIV-positive persons, have reported higher sCD14, sCD163, hs-CRP, and IL-6 levels associated with a lower CD4/CD8 ratio [ 4 , 35 ]. Specifically, Serrano-Villar et al [ 4 ] reported such associations related only to lower CD4 counts, but not higher CD8 counts, and to be absent in HIV-positive participants with >500 CD4 cells/mm 3 .…”
Section: Discussioncontrasting
confidence: 99%
“…Differences in the composition of the gut microbiome, for example, caused by specific sexual practices or frequent antibiotic use could hypothetically contribute to the lower CD4/CD8 ratios we observed in MSM. Contrary to our findings, previous studies, but conducted only in HIV-positive persons, have reported higher sCD14, sCD163, hs-CRP, and IL-6 levels associated with a lower CD4/CD8 ratio [ 4 , 35 ]. Specifically, Serrano-Villar et al [ 4 ] reported such associations related only to lower CD4 counts, but not higher CD8 counts, and to be absent in HIV-positive participants with >500 CD4 cells/mm 3 .…”
Section: Discussioncontrasting
confidence: 99%
“…In PLWHIV on cART, an association between increased CMV IgG responses and systemic inflammation, defined by increased levels of CRP, CD163, and IL-6 in serum, has previously been reported 20 , 21 , 41 , 42 , and an association between CMV-seropositivity and IL-6 levels has also been found in healthy adults 43 . However, no previous studies have addressed whether this relationship also applies to CMV-specific T-cell responses.…”
Section: Discussionmentioning
confidence: 78%
“…The frequency of CD16+CD163+ monocytes is positively correlated with the viral load. Of note, the CMV status is associated with increased levels of soluble CD163 in the plasma of HIV-infected individuals treated with ART [ 135 ]. The frequency of intermediate monocytes positively correlated with levels of the inflammation marker IL-6, the monocyte activation marker soluble CD14 (sCD14) and the cardiovascular disease marker high-sensitivity C-reactive protein (hs-CRP) [ 136 ].…”
Section: Monocytes and Hivmentioning
confidence: 99%